Variety and origin of magmas on Shatsky Rise, northwest Pacific Ocean - Takashi Sano; Kenji Shimizu; Akira Ishikawa; Ryoko Senda; Qing Chang; Jun‐Ichi Kimura; Mike Widdowson; William W. Sager (Geochemistry, Geophysics, Geosystems)
Shatsky Rise consists of thick (∼30 km maximum) basaltic crust with various geochemical compositions. Geochemistry data indicate that four magma types exist on the plateau; namely normal, low‐Ti, high‐Nb, and U1349 types. The normal type is the most abundant in volume and appears on all three large edifices of the plateau: Tamu, Ori, and Shirshov massifs. Composition of the normal type is similar to normal mid‐ocean ridge basalt (N‐MORB) composition, but with slight relative enrichment of the more incompatible elements. The low‐Ti type is distinguished from the normal type basalt by slightly lower Ti content at a given MgO. Composition of the high‐Nb type is characterized by distinctively high contents of incompatible trace elements. U1349 type basalts are composed of more primitive and depleted compositions compared with the others. The normal type basalts constitute ∼94% of the lava units of the oldest Tamu Massif and non‐normal types (i.e., the other three types) basalts comprise ∼57% on the younger Ori Massif, implying that geochemical compositions may have become heterogeneous with time. Petrological examination demonstrates that compositions of the normal‐, low‐Ti‐, and high‐Nb‐type basalts evolved through fractional crystallization of olivine, plagioclase, and augite in shallow magma chambers (<200 MPa). Model calculations of immobile trace elements estimate that the normal type basalt can be formed by ∼15% melting of a depleted mantle source in the presence of residual garnet. This degree of melting is similar to N‐MORB, but the larger effect of residual garnet during petrogenesis implies that a greater depth of melting.